«AIRES» SHARED RESEARCH FACILITIES (IPGG RAS, St. PETERSBURG): SCIENTIFIC EQUIPMENT, MAIN RESEARCH DIRECTIONS AND RESULTS - A. B. Kuznetsov; T. S. Zaitseva; E. B. Salnikova (Геодинамика и тектонофизика, 2022)
The "AIRES" Shared Research Facilities (SRF) is a high-tech laboratory complex based on the Institute of Precambrian Geology and Geochronology RAS (IPGG RAS, St. Petersburg). The Institute conducts geological, mineralogical, geochronological, isotope-geochemical and paleontological studies aimed at solving the problems of the formation and evolution of the Earth's continental crust in the Precambrian and Phanerozoic. The methodological developments of the "AIRES" SRF make it possible to interpret the conditions of occurrence of igneous, metamorphic and sedimentary rocks and minerals, as well as their age. The ongoing research includes studies on geology, geodynamics, stratigraphy, petrology, lithology, isotope geochemistry, geochronology, as well as paleogeography, archeology, soil science, ecology, and chemistry.